Management of Pregnancy in a Patient with a History of Cervical Cancer: Case Report - Sztyler-Krąkowska, Marcelina; Wąsowicz, Agnieszka; Śpiołek, Olga; Słowikowska, Aleksandra; Szatkowska, Julia; Siwiec, Jan; Smyl, Natalia; Teofilak, Mateusz; Kędziora, Franciszek (Journal of Education, Health and Sport, 2024)
Cervical cancer is one of the most common malignancies affecting women of reproductive age. Although surgical procedures such as conization or trachelectomy may offer the possibility of preserving fertility, they may also compromise cervical integrity, thereby increasing the risk of obstetric complications in subsequent pregnancies. This case report presents the management of a pregnant patient with a history of cervical cancer, thyroid dysfunction, and previous obstetric complications. The patient, a 38-year-old woman, conceived naturally after previous in vitro fertilization (IVF) attempts. Despite a complex medical history, including two prior cervical conizations for stage IA1 G1 cervical glandular carcinoma, the patient underwent successful antenatal care, delivery, and postnatal management. This report highlights the multidisciplinary approach and challenges encountered in managing pregnancies in patients with a history of cervical cancer and previous obstetric complications.